The behavior, attitude, and knowledge towards photoprotection in patients with cutaneous/systemic lupus erythematosus: a comparative study with 526 patients and healthy controls - Kumutnart Chanprapaph (2020)
© The Royal Society of Chemistry and Owner Societies 2020. Objective: To evaluate the attitude, knowledge, and behavior towards the sun protection in systemic lupus erythematosus (SLE) patients with and without cutaneous involvement (CLE) compared to non-photosensitive controls and to determine influential factors for photoprotective practices in SLE patients.Methods: A case-control study was performed. Patients and controls completed a self-reported questionnaire. For SLE patients, the presence of organ involvement, disease activity and laboratory data were acquired from their physical examination and medical records.Results: A total of 263 SLE patients and 263 healthy controls were recruited. SLE patients had statistically significant better photoprotective practices than controls,i.e.exposure to sunlight <1 hour per day (76.1%vs.48.3%, OR, 3.40; 95% CI, 2.34-4.93,p< 0.001), less outdoor activities (9.8%vs. 19.1%, OR, 0.44; 95% CI, 0.26-0.71,p= 0.003), wore long-sleeved shirts (57.0%vs. 32.7%, OR, 2.73; 95% CI, 1.92-3.89,p< 0.001) and hats (43.8%vs. 26.6%, OR 2.14; 95% CI, 1.49-3.09,p< 0.001). SLE with CLE subgroup had the highest percentage for regular practice in almost all sun protective means compared to SLE without CLE and controls. SLE with CLE patients had more diligent sunscreen application with higher percentage of consistent use (93.7%vs. 59.3%, OR, 11.66; 95% CI, 2.57-52.89,p= 0.001) and adequate application (58.1%vs. 24.6%, OR, 4.24; 95% CI, 1.93-9.30,p< 0.001) compared to those without CLE. Previous and current CLE were influential factors for adherence to photoprotective methods, while the extracutaneous involvement was not. The majority of SLE patients were well acquainted with the harm of sunlight to their diseases (91.6%). However, 40.1% of them did not perceive that sunlight could escalate their internal flare, which may have led to inferior photoprotective practices in patients with extracutaneous involvement.Conclusion: SLE patients had good awareness and practiced better photoprotection than controls. The cutaneous sign is a predictor for superior photoprotective behavior. Education regarding the harms of sunlight and the importance of appropriate photoprotection should be emphasized, especially in SLE cases without cutaneous involvement.